2018
DOI: 10.1186/s12302-018-0152-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with blooms of cyanobacteria in a large shallow lake, China

Abstract: BackgroundEutrophication of freshwater systems can result in blooms of phytoplankton, in many cases cyanobacteria. This can lead to shifts in structure and functions of phytoplankton communities adversely affecting the quality of drinking water sources, which in turn impairs public health. Relationships between structures of phytoplankton communities and concentrations of the toxicant, microcystin–leucine–arginine (MC-LR), have not been well examined in large shallow lakes. The present study investigated phyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 89 publications
2
24
0
1
Order By: Relevance
“…In spring bloom, rapid multiplication of cyanobacterial cells due to the availability of adequate amounts of nutrients, rising temperature; bright sunlight and pH were identified as the main factors for bloom formation of cyanobacteria at that time. Similar findings were also reported by Affan et al (2015) and Li et al (2018). Rahman and Jewel (2008) cells/l)ponds.…”
Section: Cyanobacterial Analysissupporting
confidence: 91%
“…In spring bloom, rapid multiplication of cyanobacterial cells due to the availability of adequate amounts of nutrients, rising temperature; bright sunlight and pH were identified as the main factors for bloom formation of cyanobacteria at that time. Similar findings were also reported by Affan et al (2015) and Li et al (2018). Rahman and Jewel (2008) cells/l)ponds.…”
Section: Cyanobacterial Analysissupporting
confidence: 91%
“…The loss of phosphorus (P) from agricultural soils has been identified as one of the main causes of eutrophication of lakes in the lower reaches of the Yangtze River in southern China [1]. Statistics have shown that major lakes and reservoirs in this area were eutrophic and mesotrophic [2][3][4], and the Yangtze River Delta region accounted for 17% of the 10 Tg annual increase in soil P around the world [2]. In soil, colloidal P (P coll ) is the P fraction bound to colloids [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, alongside this economic development, environmental issues have become increasingly prominent [1,2]. The recent outbreak of a series of environmental pollution incidents, such as the cyanobacteria in Tai Lake during the summer of 2007, the national smog in the winter of 2012, and the dead pigs floating in the Huangpu River in 2013, highlight the negative environmental externalities that accompany Chinese economic growth [3][4][5]. These problems seriously affect individuals' health and regional environmental sustainability [6,7].…”
Section: Introductionmentioning
confidence: 99%